2020
DOI: 10.1017/s0024282920000419
|View full text |Cite
|
Sign up to set email alerts
|

Lithocalla (Ascomycota, Lecanorales), a new genus of leprose lichens containing usnic acid

Abstract: The identity of Lecanora ecorticata has been uncertain due to conflicting reports of the presence of zeorin and the loss of the holotype. Phylogenetic analysis suggests that the species probably belongs in Ramalinaceae, where it is the first leprose species reported. Zeorin was found to be absent in recently collected material of L. ecorticata, including specimens from the type locality, and the report of zeorin in the lost holotype is considered to be due to contamination. A new genus, Lithocalla, is erected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…However, this is only partly true, as some lichen groups with this type of thallus (e.g., species of Lepraria neglecta group) can grow also in other habitats (e.g., Laundon 1992 ; Lendemer 2013b ). Nevertheless, the statement of Poelt (1987) was true and innovative at this time and it was later shown that the leprarioid thallus indeed originated in several unrelated lichen lineages (e.g., Ekman and Tønsberg 2002 ; Kukwa and Pérez-Ortega 2010 ; Hodkinson and Lendemer 2013 ; Malíček et al 2018 ; Guzow-Krzemińska et al 2017 ; Orange 2020 ). Furthermore, some leprarioid genera are known exclusively in sterile state, like Andreiomyces ( Arthoniales , Arthoniomycetes ), Botryolepraria ( Verrucariales , Eurotiomycetes ), Lepraria and Lithocalla (both in Lecanorales , Lecanoromycetes ) ( Ekman and Tønsberg 2002 ; Kukwa and Pérez-Ortega 2010 ; Hodkinson and Lendemer 2013 ; Orange 2020 ).…”
Section: Results and Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…However, this is only partly true, as some lichen groups with this type of thallus (e.g., species of Lepraria neglecta group) can grow also in other habitats (e.g., Laundon 1992 ; Lendemer 2013b ). Nevertheless, the statement of Poelt (1987) was true and innovative at this time and it was later shown that the leprarioid thallus indeed originated in several unrelated lichen lineages (e.g., Ekman and Tønsberg 2002 ; Kukwa and Pérez-Ortega 2010 ; Hodkinson and Lendemer 2013 ; Malíček et al 2018 ; Guzow-Krzemińska et al 2017 ; Orange 2020 ). Furthermore, some leprarioid genera are known exclusively in sterile state, like Andreiomyces ( Arthoniales , Arthoniomycetes ), Botryolepraria ( Verrucariales , Eurotiomycetes ), Lepraria and Lithocalla (both in Lecanorales , Lecanoromycetes ) ( Ekman and Tønsberg 2002 ; Kukwa and Pérez-Ortega 2010 ; Hodkinson and Lendemer 2013 ; Orange 2020 ).…”
Section: Results and Discussionmentioning
confidence: 95%
“… Pseudolepraria is the first genus forming leprose and sterile thalli that can be placed with high support within Ramalinaceae . Orange (2020) described the genus Lithocalla and placed it with uncertainty in Ramalinaceae . In our phylogeny, Lithocalla forms the sister group to Ramalinaceae sensu Kistenich et al (2018) , but this may be an artifact of the taxon sampling.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations